Enantioselective synthesis of the essential oil and pheromonal component ar-himachalene by a chiral pool and chirality induction approach - Chavan, Subhash P.; Khatod, Harshali S. (Tetrahedron-Asymmetry, 2012)
The enantioselective synthesis of both isomers of ar-himachalene has been achieved starting from enantiomerically pure citronellal and p-methyl alpha-methyl styrene as an application of a chiral pool and chirality induction approach, respectively. The key reactions involved in the synthesis include the Sharpless asymmetric dihydroxylation for the induction of chirality at benzylic carbon bearing the methyl group and the use of a hypervalent iodine reagent or trimethylsilyldiazomethane (TMSCHN2) for the six to seven membered ring expansion. (C) 2012 Elsevier Ltd. All rights reserved.

Exploration of the diastereoselectivity in an unusual Grignard reaction and its application towards the synthesis of styryl lactones 7-epi-(+)-goniodiol and 8-epi-(-)-goniodiol - Chavan, Subhash P.; Khatod, Harshali S.; Das, Tamal; Vanka, Kumar (RSC Advances, 2016)
An unusual diastereoselective Grignard reaction is explored, where the Grignard reagents are derived from 1,n-dihaloalkanes. A steric bias due to the presence of a quaternary centre adjacent to the acetonide ester at the benzylic position is responsible for the formation of an intramolecularly reduced product in almost quantitative yield. This steric hindrance is responsible for the diastereoselectivity observed with a variety of aromatic as well as aliphatic esters. The unusual Grignard reaction furnishes long chain secondary alcohols possessing a terminal olefin, which are synthetically important intermediates. As an application of this method, the diastereoselective synthesis of styryl lactones viz. 7-epi-(+)-goniodiol (29) and 8-epi(-)-goniodiol (30) has been achieved.

Application of unusual grignard reaction for the stereoselective synthesis of antidepressant drug (R)-(-)-venlafaxine - Chavan, Subhash P.; Khatod, Harshali S. (Synthesis-Stuttgart, 2017)
An enantioselective synthesis of antidepressant drug (R)-(-)-venlafaxine is accomplished as an application of recently explored unusual Grignard reaction. An innovative method for the generation of chirality at extremely reactive benzylic center along with determination of absolute stereochemistry has been discussed. The key steps involved in the synthesis include Sharpless asymmetric dihydroxylation for the induction of chirality and an unusual Grignard reaction.